Integration of a new sensing controller for marine pollutant monitoring using field effect devices - Parreira, Carolina dos Santos (2024)
The preservation of the oceans is an urgent global issue driven by increasing pollution in marine eco- systems, which negatively impacts marine life and leads to long-term ecological damage. To mitigate these effects, it is essential to develop innovative technologies that can monitor pollutants, particularly heavy metals, with greater accuracy and accessibility, overcoming the limitations of current solutions. This work is part of the SeaSenseX project and aims to develop a portable device equipped with sensors based on the CMISFET (Charge-Modulated-Ion-Sensing-Field-Effect-Transistor) architecture. This device utilizes a control electrode and a sensitive area to modulate the channel of an integrated MOS (Metal-Oxide- Semiconductor) transistor. The sensors are fabricated on flexible PEN substrates at CENIMAT|I3N and were tested using two methodologies: i) an existing semiconductor parameter analyzer in the laboratory, and ii) a PCB (Printed Circuit Board) connected to an Arduino for real-time data acquisition. Two types of MOSFETs, a commercial (CD4007UB) and one especially developed for this project (MKProt), were compared in meas- urements conducted with pH buffer solutions. Moreover, a microfluidic system was developed and tested to optimize the sensitivity of the sensors. This improvement allowed for this technology to go from a reported sensitivity of 39 ± 1 mV/pH to 54 ± 1 mV/pH, close to the theoretical maximum of approximately 59 mV/pH unit. The MKProt MOSFET, which demonstrated significant advantages in data acquisition, was utilized for measurements with mercury chloride and cadmium chloride solutions. The device successfully detected mercury concentrations ranging from 1 ppm to 15 ppm and cadmium concentrations between 1000 ppm and 3000 ppm. The recorded sensitivities for de- tecting these metals are 0.11 ± 0.01 mV/Log(ppm) for mercury and 0.41 ± 0.01 mV/ppm for cadmium, respec- tively. In addition, preliminary analyses were performed using membranes impregnated with silver nanoparti- cles (Ag-NPs) deposited on Nafion on the sensor surface. These analyses aimed to explore options for opti- mizing heavy metal detection. However, further research is necessary to assess the impact of these modifica- tions and ensure the reliability and performance of the sensors in real-world applications.